Political institutions and collective attachments. (December 2019) - Aksoy, Deniz; Hadzic, Dino
We argue that the geographic distribution of power across different levels of government influences citizens' attachments to alternative collective groups. In federal states where authority is shared between the center and regions, individuals are more likely to have attachments to multiple groups. We present evidence for the impact of state structure on collective attachments using the case of supranational European identity. We show that in countries where state structure empowers sub-state governments, individuals manifest stronger attachments to a supranational European community than they do in unitary states. This study indicates that when we examine individuals' attachments to a collective group, the political-institutional context in which these individuals are embedded is an important factor to consider.